The invention of rare books : private interest and public memory, 1600-1840 - McKitterick, David, 1948- (Cambridge University Press, 2018)
"When does a book that is merely old become a rarity and an object of desire? David McKitterick examines, for the first time, the development of the idea of rare books, and why they matter. Studying examples from across Europe, he explores how this idea took shape in the sixteenth and seventeenth centuries, and how collectors, the book trade and libraries gradually came together to identify canons that often remain the same today. In a world that many people found to be over-supplied with books, the invention of rare books was a process of selection. As books are one of the principal means of memory, this process also created particular kinds of remembering. Taking a European perspective, McKitterick looks at these interests as they developed from being matters of largely private concern and curiosity, to the larger public and national responsibilities of the first half of the nineteenth century"--